Potencial climático da viticultura na microrregião de Mossoró/RN - Oliveira, Francisca Sonally de (Universidade Federal Rural do Semi-Árido, 2014)
The Geoviticultural Multicriteria Climatic Classification System was developed with the goal of improving characterization of viticultural climate. It consists of three viticulture climatic indices: Heliothermal (IH), and Cool Night Index (IF) and Dryness Index (IS). The objective of this study was to analyze the potential of micro-climate of Mossoró/RN for the production of table grapes, based on CCM Geoviticultural System. Grapes produced in the region were analyzed, with the aim of comparing the final quality of the fruit produced in the semi-arid climate. The municipality of Mossoró/RN is located 18 m above sea level, 5° 11' S and 37° 20' W. The climate is Bswh '. The average maximum temperature range from 32.1 to 34.5ºC and the average minimum between 21.3 and 23.7ºC; the average annual rainfall is 673 mm. Data for the study were obtained from the meteorological station of UFERSA, corresponding to historical series 1978 - 2007, constituting the values of air temperatures - minimum, average and maximum - the monthly rainfall and potential evapotranspiration of the region. CCM Geoviticulture System was used. We carried out the calculation for two distinct periods: from April 1st to September 30 (AW period - autumn-winter) and October 1st to March 31st (SSu period - spring-summer). The IS, IH and IF indices were compared with the tabulated values. The micro-region of Mossoró/RN, especially from the climatic point of view, is suitable for viticulture
Climatic Potential for viticulture in the micro megion of Mossoró/RN
Keywords: Climate; Climate indices; CCM system Geoviticulture; Climatic zoning; Clima; Índices climáticos; Sistema CCM Geovitícola; Zoneamento climático; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA